Portfolio as an assessment tool and its implementation in Malaysian ESL classrooms: a study in two secondary schools - Swaran Singh, Charanjit Kaur; Abdul Samad, Arshad (Universiti Putra Malaysia Press, 2013)
This research presents the findings of a study relating to portfolio as an assessment tool and its implementation by English as Second Language (ESL) teachers in two secondary schools. Participants included nine lower and upper secondary school classroom ESL teachers. The research design was qualitative in nature as there was a need to immerse in the classroom to witness and observe the portfolio assessment process carried out by the ESL teachers. The interviewing technique was used for triangulating data obtained during classroom observations. Data collected through both techniques were transcribed and analyzed manually. The nine ESL teachers involved felt that the current assessment methods were insufficient for measuring student learning as students focused on memorization and studied merely for examination rather than the acquisition of knowledge. Significantly, the teachers divulged that when students are engaged in portfolio assessment, they become less examination oriented and are able to take charge of their learning. The teachers reported that although the implementation of portfolio as an assessment tool involved major investment in time, they proved to be valuable and conducive tools for individualizing the learning process and in documenting student progress and achievement over time. Findings from this study recommend that portfolios drive instruction by assisting teachers to identify student needs by matching instruction to needs and assessment to instruction. The results have clear implications for assessment, and the teaching and learning of second language learning.